AUDIT AKUN PERSEDIAAN PADA PT HJMI OLEH KAP HELIANTONO DAN REKAN - Amelia, Maria Leona; Wijaya, Indra (JURNAL MAHASISWA BINA INSANI, 2023)
This research was motivated by problems related to recording inventory that was missed and misplaced inventory that did not match the stock-taking report. This research aims to find out whether the inventory recording audit procedures are by applicable accounting standards. The research method used in this research is descriptive qualitative using data collection techniques through observation, interviews, and documentation. PT HJMI itself focuses on supplying medical equipment such as masks, stethoscopes, and gloves with quite a significant value. Some inventory at PT HJMI is placed in different places, causing differences in calculations. This was obtained because PT HJMI confirmed the differences in physical calculations found by the auditors by providing stock-taking reports and minutes. The results of this research explain that the implementation of recording inventory account audit procedures at PT HJMI is by applicable financial accounting standards. The auditor suggested that PT HJMI inventory be registered according to inventory placement in the same warehouse and be easily accessible to make it easier for PT HJMI to carry out internal controls.